Adaptor proteins: Flexible and dynamic modulators of immune cell signalling. (27th October 2020) - Borowicz, Paweł; Chan, Hanna; Hauge, Anette; Spurkland, Anne
Abstract: To maintain homeostasis, all cells respond to environmental cues via a multitude of surface receptors. In order to act appropriately in their environment, cells are dependent on the transduction of the incoming signal through tightly regulated and interconnected signalling pathways to the cell nucleus. In particular, cells implicated in the immune system greatly depend on such systems to respond in a flexible and dynamic manner to environmental challenges. One major group of intracellular proteins that are involved in these signalling pathways are adaptor proteins. Although adaptor proteins are essential for normal immune cell operation, the functional role of this group of signalling proteins remains to be fully appreciated. So far, research on adaptor proteins has revealed their unique potential in building transient complexes in a reversible, dynamic and inducible manner. In this review, we explore the roles of adaptor proteins – in space and time of intracellular signalling – and their associations with human disease. Examples of adaptor proteins expressed in hematopoietic cells highlight their crucial role in the immune system. Lastly, we present challenges faced in elucidating roles of adaptor proteins, as illustrated by the T cell–specific adaptor (TSAd) protein encoded by the SH2D2A gene.